Selection of Electric Motor for Electric Go Kart Performance - Muhammad Azhad Amin bin Fauzi, (Progress in Engineering Application and Technology, 2022)
Electric Go Kart have been designed to help decrease the pollution emitted and as a substitute to the typical combustion engine vehicle. However, due to its high congestion and pollution issue, a pollution with free vehicle needs to be created. The aim of the project is to select an electric drive system. However, this report will have a more detailed about electric motor and calculations for powertrain of the project. In the first phase of the project, the author surveyed information related to the typical of electric motor that use in electric go kart. Most of the method used in the project is by analytical calculations since it requires building a prototype. The second phase of the project is mainly on calculating the forces acted on the Electric Go Kart itself. It is to ensure that the drive power of the designed can overcome the forces acting on it. A dynamic analysis was performed to determine the power required to drive the E-Go Kart at the specified mode of motion. After that, the author selects drive system components with required specifications. The electric motor selected is based on output, voltage, current, compatibility of the Electric Go Kart and comfort of the users. Analysis on the electric motor is needed to make sure that the performance is the same if not better than the set specifications set in the objectives. Towards the end phase of the project, the author may provide a prototype of Electric Go Kart to analyse the actual situation when the electric motor run the go kart. In conclusion, if the project is a success, then it will help the student to produce a less pollution vehicle with high power and torque which indirectly help the consumers to switch from combustion engine go kart to electric motor go kart.